Moderation of neoclassical impurity accumulation in high temperature plasmas of helical devices. (27th October 2016) - Velasco, J.L.; Calvo, I.; Satake, S.; Alonso, A.; Nunami, M.; Yokoyama, M.; Sato, M.; Estrada, T.; Fontdecaba, J.M.; Liniers, M.; McCarthy, K.J.; Medina, F.; et al.
Abstract: Achieving impurity and helium ash control is a crucial issue in the path towards fusion-grade magnetic confinement devices, and this is particularly the case of helical reactors, whose low-collisionality ion-root operation scenarios usually display a negative radial electric field which is expected to cause inwards impurity pinch. In this work we discuss, based on experimental measurements and standard predictions of neoclassical theory, how plasmas of very low ion collisionality, similar to those observed in the impurity hole of the large helical device (Yoshinuma et al and The LHD Experimental Group 2009 Nucl. Fusion 49 062002, Ida et al and The LHD Experimental Group 2009 Phys. Plasmas 16 056111 and Yokoyama et al and LHD Experimental Group 2002 Nucl. Fusion 42 143), can be an exception to this general rule, and how a negative radial electric field can coexist with an outward impurity flux. This interpretation is supported by comparison with documented discharges available in the International Stellarator-Heliotron Profile Database, and it can be extrapolated to show that achievement of high ion temperature in the core of helical devices is not fundamentally incompatible with low core impurity content.